Advanced hepatocellular carcinoma: Impact of systemic treatments on health‐related quality of life and patient‐reported outcomes. Issue 2 (25th April 2022) - Aimar, Giacomo; Marino, Donatella; Zichi, Clizia; Gamba, Teresa; Caglio, Andrea; De Vita, Francesca; Sperti, Elisa; Di Maio, Massimo
Abstract: In the past years, treatment options for advanced hepatocellular carcinoma (HCC) have thriven. Although globally recognised, the patient‐reported outcomes (PROs) are often underused and quality of life (QoL) results are underreported in many phase III trials. We performed a systematic review to describe the prevalence of QoL inclusion and heterogeneity in QoL reporting in published phase III trials of systemic treatment in advanced HCC. Twenty‐one publications were identified: 12 (57.1%) in first line setting, eight (38.1%) in second line and only one (4.7%) in second and further lines. In 14 trials (66.6%), Qol was included in the analysis as a secondary or tertiary endpoint but only in nine (47.4%) cases Qol results were published in the main paper. QoL data are lacking in a significant proportion of published phase III trials in advanced HCC. The methodology of QoL analysis is heterogeneous for type of instruments, analysis and presentation of results. Abstract : In the past years treatment options for advanced hepatocellular carcinoma (HCC) have thriven. Patient‐reported outcomes (PROs) are often underused in many phase III trials. We performed a systematic review to describe PROs.